Effects of parasites upon non-host predator avoidance behaviour in native and invasive gammarids - Farahani, Sajad; Palsbøll, Per J.; Pen, Ido; Komdeur, Jan (Parasitology, 2021)
The acanthocephalan parasite, Polymorphus minutus, manipulates its intermediate hosts' (gammarids) behaviour, presumably to facilitate its transmission to the definitive hosts. A fundamental question is whether this capability has evolved to target gammarids in general, or specifically sympatric gammarids. We assessed the responses to chemical cues from a non-host predator (the three-spined sticklebacks Gasterosteus aculeatus) in infected and non-infected gammarids; two native (Gammarus pulex and Gammarus fossarum), and one invasive (Echinogammarus berilloni) species, all sampled in the Paderborn Plateau (Germany). The level of predator avoidance was assessed by subjecting gammarids to choice experiments with the presence or absence of predator chemical cues. We did not detect any behavioural differences between uninfected and infected G. pulex and E. berilloni, but an elevated degree of predator avoidance in infected G. fossarum. Avoiding non-host predators may ultimately increase the probability of P. minutus' of predation by the definitive host. Our results suggested that P. minutus' ability to alter the host's behaviour may have evolved to specifically target sympatric gammarid host species. Uninfected gammarids did not appear to avoid the non-host predator chemical cues. Overall the results also opened the possibility that parasites may play a critical role in the success or failure of invasive species.